Stratigraphy and sedimentology of the Permian of the Falkland Islands; lithostratigraphic and palaeoenvironmental links with South Africa - Trewin, N. H; Macdonald, D. I. M; Thomas, C. G. C (Journal of the Geological Society, 2002)
Comparison of the facies, ichnology and palaeocurrent patterns of the Permian of the Falkland Islands and the Dwyka, Ecca and Beaufort (part) groups in South Africa supports the hypothesis that the Falkland Islands lay east of South Africa in a rotated position prior to continental break-up. Key sections in the Falklands (NW Lafonia) and the Eastern Cape (Ecca Pass) would have lain about 200 km apart in Permian time. In the absence of accurate chonostratigraphic and biostratigraphic information from the Permian of the Falkland Islands, emphasis is placed on lithostratigraphic comparison. The Permian successions in both areas pass from diamictite through basin floor sediments, including organic-rich shale, rhythmites and turbidites. Mud-dominated delta front deposits culminating in channel deposits of a generally subaqueous delta top overlie the basin floor sediments. Points of close lithostratigraphic comparison are: (1) the diamictites have identical appearance, facies, and compatible palaeocurrents; (2) glacial sections are overlain by organic-rich black shales; (3) K-bentonites occur in basin-floor successions; (4) presence of basin-floor turbidite sandstone units with interbedded rhythmite units, and a distinctive Umfolozia/Undichna ichnofauna; (5) coarsening-up delta-front sequences are overlain by fining-up channel sandstone facies; (6) there is a close petrographic similarity indicating derivation of sandstones from a contemporaneous volcanic arc. The Permian successions of the two areas form parts of the fill of the eastern end of the main Karoo Basin, and were subject to the same influences of tectonic development, sediment derivation, eustatic variation and climatic change.